2013
DOI: 10.1016/j.molcel.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Splicing-Factor Oncoprotein SRSF1 Stabilizes p53 via RPL5 and Induces Cellular Senescence

Abstract: SUMMARY Splicing and translation are highly regulated steps of gene expression. Altered expression of proteins involved in these processes can be deleterious. Therefore, the cell has many safeguards against such misregulation. We report that the oncogenic splicing factor SRSF1, which is overexpressed in many cancers, stabilizes the tumor-suppressor protein p53 by abrogating its MDM2-dependent proteasomal degradation. We show that SRSF1 is a necessary component of an MDM2/ribosomal-protein complex—separate from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 42 publications
3
82
0
2
Order By: Relevance
“…SRSF1 was repressed by both doxorubicin and nutlin-3a treatments particularly in the subpolysomal RNA fraction, and the p53-dependent negative modulation was apparent comparing MCF7vector with MCF7shp53 cells. As it was recently reported that SRSF1 overexpression provides resistance to oncogenic transformation via stabilization of p53, 30,49 we propose that we have uncovered a negative feedback loop by which p53 inhibits a positive regulator.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…SRSF1 was repressed by both doxorubicin and nutlin-3a treatments particularly in the subpolysomal RNA fraction, and the p53-dependent negative modulation was apparent comparing MCF7vector with MCF7shp53 cells. As it was recently reported that SRSF1 overexpression provides resistance to oncogenic transformation via stabilization of p53, 30,49 we propose that we have uncovered a negative feedback loop by which p53 inhibits a positive regulator.…”
Section: Discussionmentioning
confidence: 54%
“…We confirmed data indicating that SRSF1 reduction leads to a lower stabilization of p53 protein and to lower induction of p21. 30,38 We then examined c-MYC protein levels, given that c-MYC translation is reported to be upregulated by YBX1, 39 and SFSRF1 depletion was associated with reduced c-MYC oncogenicity. 36 Interestingly, silencing SRSF1 led to a concomitant decrease in YBX1 protein and even more so in the c-MYC protein.…”
Section: Resultsmentioning
confidence: 99%
“…The splicing pattern of the MCL-1 gene has been reported to correlate with the sensitivity of a wide variety of tumor cells to cytotoxic agents (Palve and Teni 2012;Gao et al 2013;Pennarun et al 2013). Recent studies have demonstrated a link between the up-regulation of the MCL-1 L transcript and SR proteins, such as SRSF1 and SRSF5 (Gautrey and TysonCapper 2012), which act as proto-oncogenes in various types of cancer (Das et al 2012;Breig and Baklouti 2013;Fregoso et al 2013). An increase in SRSF1 has been demonstrated to facilitate the translational efficiency and stability of the MCL-1 L isoform in breast cells (Gautrey and Tyson-Capper 2012).…”
Section: Discussionmentioning
confidence: 99%
“…p53 induction is one of the primary responses to SRSF1 overexpression in primary human and murine fibroblasts, and results in cells entering a state of premature cellular senescence (Fregoso et al 2013). Briefly, SRSF1 plays a role in the nucleolar stress pathway, by stabilizing the interaction between ribosomal protein RPL5 and the E3 ubiquitin ligase MDM2 FIGURE 3.…”
Section: Srsf1-serine/arginine-rich Splicing Factormentioning
confidence: 99%